Relative Abundance and Diversity of Bacterial Methanotrophs at the Oxic–Anoxic Interface of the Congo Deep-Sea Fan - Bessette, Sandrine; Moalic, Yann; Gautey, Sébastien; Lesongeur, Françoise; Godfroy, Anne; Toffin, Laurent (Frontiers in Microbiology, 2017)
Sitting at ~5 000 m water depth on the Congo-Angola margin and ~ 760 km offshore of the West African coast, the recent lobe complex of the Congo deep-sea fan receives large amounts of fluvial sediments (3-5% organic carbon). This organic-rich sedimentation area harbors habitats with chemosynthetic communities similar to those of cold seeps. In this study, we investigated relative abundance, diversity and distribution of aerobic methane-oxidizing bacteria (MOB) communities at the oxic-anoxic interface of sedimentary habitats by using fluorescence in situ hybridization and comparative sequence analysis of particulate mono-oxygenase (pmoA) genes. Our findings revealed that sedimentary habitats of the recent lobe complex hosted type I and type II MOB cells and comparisons of pmoA community compositions showed variations among the different organic-rich habitats. Furthermore, the pmoA lineages were taxonomically more diverse compared to methane seep environments and were related to those found at cold seeps. Surprisingly, MOB phylogenetic lineages typical of terrestrial environments were observed at such water depth. In contrast, MOB cells or pmoA sequences were not detected at the previous lobe complex that is disconnected from the Congo River inputs.